Revisão integrativa sobre o uso de anticoncepcionais orais no tratamento da síndrome dos ovários policísticos (SOP) - Farias, Amanda Cristine Marques (Brasil, 2024)
Polycystic Ovary Syndrome (PCOS) is an endocrine dysfunction in women of reproductive age. This endocrine disorder presents typical characteristics of excess androgen hormones, such as hyperandrogenism in varying degrees and chronic anovulation. Among the therapeutic modalities for this disorder, there are non-pharmacological treatments and pharmacological treatment, such as the use of oral contraceptives, which is the focus of this work, and other medications such as Metformin, Letrozole, Clomiphene Citrate, herbal remedies and medicinal herbs. Oral contraceptives are used as the first line of treatment for women with PCOS, especially for those who are not planning to become pregnant at the moment. As with all medications, there are beneficial and harmful effects to the use of oral contraceptives. The benefits of this method include regulating the menstrual cycle, treating acne, controlling hormones, reducing ovarian cysts, among others. The objective of this study was to conduct an integrative review to evaluate the therapeutic efficacy of oral contraceptives in the treatment of PCOS, highlighting the latest innovations and advances in therapy. This research employed an integrative review methodology, searching for relevant studies in the Google Scholar, Scielo, BVS, PubMed, and Lilacs databases. The research had inclusion and exclusion criteria. For the inclusion criteria, articles published between 2014 and 2024 that addressed the use of oral contraceptives in the treatment of Polycystic Ovary Syndrome (PCOS) were selected, and only articles available in full and free of charge in Portuguese were considered. For exclusion criteria, duplicate review articles, articles that did not address the topic satisfactorily, that did not present complete data on the use of contraceptives in treatment, and that were published more than 10 years ago were excluded. A total of 12 studies were selected and, according to the authors, it was concluded that oral contraceptives are effective in controlling symptoms, but cause adverse effects when compared to other therapies. Although other therapeutic options are also effective, a set of more in-depth studies is important, especially in the treatment with phytotherapeutics and herbs, since PCOS is considered a very complex condition.